HILITE – A well-defined ion target for laser experiments. Issue 9 (January 2020) - Stallkamp, N; Ringleb, S; Arndt, B; Kiffer, M; Kumar, S; Paulus, G G; Quint, W; Stöhlker, Th; Vogel, M
Synopsis: We present a Penning-trap-based setup for the study of light-matter interactions in the high-power and/or high-intensity laser regime, such as multi-photon ionization and field ionization. The setup applies ion-cloud formation techniques to highly charged ions to the end of specific target preparation, as well as non-destructive detection techniques to identify and quantify the interaction educts and products.